Russian Bible wars: modern scriptural translation and cultural authority - Batalden, Stephen K. (Cambridge University Press, 2013)
Although biblical texts were known in Church Slavonic as early as the ninth century, translation of the Bible into Russian came about only in the nineteenth century. Modern scriptural translation generated major religious and cultural conflict within the Russian Orthodox church. The resulting divisions left church authority particularly vulnerable to political pressures exerted upon it in the twentieth century. Russian Bible Wars illuminates the fundamental issues of authority that have divided modern Russian religious culture. Set within the theoretical debate over secularization, the volume clarifies why the Russian Bible was issued relatively late and amidst great controversy. Stephen Batalden's study traces the development of biblical translation into Russian and of the 'Bible wars' that then occurred in the nineteenth and twentieth centuries in Russia. The annotated bibliography of the Russian Bible identifies the different editions and their publication history.